Myth in the structure of a narrative text (Modern Kazakhstani prose as a case study) (Eurasian Journal of Philology Science and Education, 2021)
The article is devoted to the study of classical/ancient myths. It functions in modern literary works in the form of "fragments" (images and motives). These images and motives are inserted in the narrative text, these elements of poetics are most productive to analyze. To trace the forms of existence, evolution and transformation of myth in the literature of the modern period. Classical myth as a prospectively directed source of inter-textuality is interspersed in a modern work, as a way of artistic organization of the material, and gives a special worldview.The study of the reflection of the myth is also in demand in the internal cultural policy of the Republic of Kazakhstan in connection with the actualized processes of national self-identification, cultural and mental specifics of the Kazakh ethnic group and other peoples of our multinational country. Modern man does not deal with archaic myths as creations of collective fantasy, but with their literary treatments placed in a different space-time continuum. When actualized in a literary text, the myth as a precedent text loses its independence, acquiring a new contextual meaning. One of the main features of the new mythological prose is the introduction of peculiar layers of national identity into the plot. Thanks to the most significant constants of existence, mythological elements are spilt into the individual author's vision.Keywords: myth, a new myth, prose, mythological consciousness, classical myth.